Needs Analysis of Learning Video Development Using Edpuzzle Based Problem Based Learning to Improve Critical Thinking Skills of High School Students - Hartati, Fitri Dwi; Islami, Nur; Rahmad, M. (Journal of Educational Sciences, 2023)
This study aims to determine the extent to which the development of learning videos using Edpuzzle based on Problem Based Learning is needed. The research method used is a survey method where the researcher collects data on the analysis of the needs of teachers and students as well as data on student characteristics through the distribution of questionnaires. Needs analysis data were obtained from 28 teachers and 79 students while student characteristics data were obtained from 93 students in the Riau province education office. Based on the results of the needs analysis, namely from the aspect of the subject, object, process, and learning media, there are 81.3% of teachers in the very high category and 70.1% of students in the high category stating that the development of learning videos using Edpuzzle based Problem Based Learning needs to be done to improve students' critical thinking skills on direct current circuit material. Meanwhile, based on the results of the analysis of student characteristics, 64.6% of students stated that the need for developing learning videos using Edpuzzle based Problem Based Learning to improve students' critical thinking skills was in the high category, so that the development of learning videos using Edpuzzle based Problem Based Learning to improve students' critical thinking skills at direct current circuit material can be done.